New skills for the 21st century lawyer students - Bergsaker, Anne Schad; Westbye, Hilde; Gasparini, Andrea (Septentrio Conference Series, 2021)
For the future lawyer digital skills will become valuable, but at the moment there are few opportunities to acquire advanced digital skills through the master’s of law programme at the University of Oslo. One new elective course, “Legal Technology: Artificial Intelligence and Law”, have experimented on how different advanced skillsets can be achieved in a short period of time. In this paper we present our findings and experiences when library and technical staff from the University of Oslo worked together with the Faculty of Law, in developing a non-mandatory law-AI boot-camp.The AI boot-camp had six lectures and workshops and gave a practical view on AI and technological skills. Three lessons on python were given by the company Synch Law1 and library staff. The library gave the second lesson on python trying out a carpentry approach. There was also one workshop about Design Thinking (Brown, 2009) given by the library, and Microsoft gave one lecture about AI and the Azure platform. The last lesson was about digital mentoring held by one of the course tutors.The library had already worked on the use of AI at the University (Gasparini et al., 2018), but not in the context of legal education. By challenging the law students with different innovative practices, we observed that a deeper understanding of AI and technological skills emerged. The law students became more creative when they were exposed to multidisciplinary methods (Seidel & Fixson, 2013).Our findings support the new role the library can have as a partner when new forms of learning and knowledge are created. The library possesses a range of new competencies needed at the University. However, there should be more cross departmental collaboration.